A comparison of desorption process of Chinese and Australian lignites by dynamic vapour sorption. Issue 8 (23rd May 2016) - He, Qiongqiong; Huang, Shaomeng; Wan, Keji; Xu, Hongxiang; Miao, Zhenyong
ABSTRACT: Modified BET model and Do and Do (D.D.) model were chosen to interpret the desorption process of water on hard and soft lignites. The organic and inorganic hydrophilic sites were determined by X-ray photoelectron spectroscopy and X-Ray fluorescence spectroscopy. From the modified BET model, only a small part of hydrophilic sites (HSs) acted as effective primary sites due to space restraint, intramolecular hydrogen bond and maybe more than one hydrophilic site connecting with one water molecule. From the D.D. model, the total adsorption sites (St ) of Loy Yang lignite (LY) is 18.7 mmol/g, which is higher than that of Shengli (SL) 17.0 mmol/g in spite of lower primary sites, and the saturation concentration of water (qus ) in the micropore of LY is 33.7 mmol/g, which is much higher than that of SL (12.5 mmol/g). So the high moisture-holding capacity of LY is mainly determined by the high St and qus, and not the primary sites. The size of water clusters entering the micropores is 7 for SL and 6 for LY, which is related to relative location of HS. When dewatered, the higher total sites density and smaller water cluster size of LY both implied higher dewatering energy.